Diversity of Financial Products and Services in Global Markets - Lallang, Sugiarto (Advances in Economics & Financial Studies, 2024)
This study aims to explore the diversity of financial products and services in global markets, examining consumer behavior, regulatory challenges, and market dynamics. Utilizing qualitative research methods, interviews were conducted with stakeholders from various sectors of the financial industry. The findings revealed the complex interplay of psychological, socio-economic, and situational factors influencing consumer perceptions and preferences. Participants highlighted challenges in understanding complex financial products and emphasized the pivotal role of regulatory bodies in promoting transparency and safeguarding consumer interests. Regulatory disparities and cross-border capital flows were identified as formidable obstacles, underscoring the need for international cooperation. The study's implications include the importance of targeted interventions to enhance consumer empowerment, strengthen regulatory oversight, and foster global collaboration in navigating the complexities of the financial landscape.